The effect of green tea (Camellia sinensis) on lipid profiles and renal function in people with type 2 diabetes and nephropathy: a randomized controlled clinical trial - Yazdanpanah, Zeinab; Salehi-Abargouei, Amin; Mozaffari, Zohre; Hemayati, Roya (Frontiers in Nutrition, 2023)
Introduction: Diabetic nephropathy is one of the most important microvascular complications of diabetes. Despite the modern treatments, herbs or medicinal plants have gained wide attention. One of these herbs is green tea (Camellia sinensis), which may have an impact on renal function, lipid profiles, and HbA1c. However, the evidence for this is unclear and limited. The present study aimed to evaluate the effect of different doses of green tea on these parameters in type 2 diabetes patients (T2DM) with nephropathy. Methods: Sixty-six individuals with T2DM nephropathy (aged 30–70 years) were randomly assigned to receive three cups of green tea/day (n= 22), two cups of green tea/day (n= 22), and the control group (n= 22) for 12 weeks. Lipid profiles, glycated hemoglobin A1c (HbA1c), and renal markers were measured before and after intervention. Data were analyzed using SPSS software version 23. One-way analysis of variance (ANOVA), least significant difference (LSD) post-hoc, and analysis of covariance were used to compare quantitative variables. Results: In total, 64 participants completed the study. Consuming three cups of infusion green tea per day (7.5 gr) led to a significant reduction in serum levels of total cholesterol (p= 0.009) and HbA1c (p= 0.006) and increased in high-density lipoprotein cholesterol (HDL-C) (p= 0.02) compared with the control group who did not drink green tea. However, no significant differences were observed for other variables. Conclusion: In general, it was found that drinking three cups of green tea infusion (7.5 gr) per day produced beneficial effects on some lipid profiles and HbA1c without any adverse effects on renal function in patients with T2DM nephropathy. More studies are needed to fully elucidate these findings.